PELATIHAN DAN PENDAMPINGAN SISTEM KEUANGAN TERKOMPUTERISASI UNTUK KEBERLANJUTAN USAHA UMKM - Ni Putu Yeni Astiti; I Nyoman Jayanegara; I Made Suryana Dwipa (Universitas Mataram, 2025)
In today's digital age, the use of computerized financial reporting systems has become an urgent need for MSMEs to be able to compete and survive in the long run. Therefore, intervention in the form of training and mentoring is needed, focusing on increasing the capacity of MSME actors in preparing technology-based financial reports. Based on initial interviews with the business owner, it was found that the financial record-keeping system is still done simply and is not structured, only recording sales on sales invoices. Sales and purchase transactions are only recorded manually on sales invoices without any periodic financial statements. The purpose of this Community Partnership Service activity is to apply accounting bookkeeping applications to record business transactions in order to generate accurate financial statements. The benefits of this service activity are to increase business competitiveness and sustainability. The implementation method for this activity includes several stages. The first stage of the service activity was for the service team to conduct interviews and discussions with the owner of the Asri Dewi MSME. The second stage was for the service team to provide material on simple bookkeeping that could be used by MSMEs. The third stage was for the service team to conduct simulations on recording financial statements. The fourth stage is monitoring and evaluation. The monitoring and evaluation results show that financial recording thru the computerized financial system has met the activity's objectives. The post-test results showed an average increase of 50% compared to the pre-test results, indicating an improvement in the partners' conceptual understanding of computerized financial systems, the functions of Microsoft Excel in financial record-keeping, and awareness of the importance of efficiency and accuracy in managing business finances. This reflects the success of the mentoring activities in improving digital financial literacy and competence at the knowledge level.